Teacher Engagement as a Multidimensional Construct: Insights From a Measurement Model Analysis - Hidayati, Nurkhairo; Armayati, Leni; Kalsum, Ummi; Putri, Iffa Ichwani (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to evaluate teacher engagement as a multidimensional, reflective construct comprising four dimensions: academic support, emotional support, guidance support, and assessment support. This study employed a quantitative approach with a survey design using cluster sampling across four public senior high schools. A total of 1.359 eleventh-grade students from four public senior high schools in Pekanbaru participated by completing a 24-item questionnaire, which was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). This study used a reflective–reflective hierarchical component model, in which both the first-order dimensions and the second-order teacher engagement construct were specified as reflective. The results indicate that all indicators exhibited outer loading values above 0.70, and each dimension met the criteria for internal reliability and convergent validity, with an average variance extracted (AVE) of 0.573–0.639. Discriminant validity was also established based on the Fornell–Larcker criterion and the HTMT ratio. At the higher-order level, teacher engagement demonstrated excellent reliability, despite the AVE value being below the conventional threshold, a common outcome in reflective hierarchical models. All four dimensions contributed significantly to the higher-order construct, with emotional support emerging as the dominant component. These findings highlight that teacher engagement in the Indonesian context is perceived as a multidimensional phenomenon strongly shaped by teachers’ emotional and instructional support. The measurement model developed in this study provides a solid foundation for future research and the development of interventions to enhance teaching quality in schools.